SUSU KEDELAI MENURUNKAN TEKANAN DARAH SISTOLIK DAN DIASTOLIK PADA IBU HAMIL PRE-HIPERTENSI - Niken Wening; Suyatno Suyatno; Siti Fatimah Pradigdo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Hypertension in pregnancy have an impact on maternal and child mortality which can be prevented by intake of antioxidants (flavonoids), one of which is sourced from soy milk. The purpose of this study was to analyze the effect of soy milk consumption against systolic and diastolic blood pressure in pregnant women. This research was Quasi Experimental with pretest-posttest control group design. The population were pregnant women in the work area of Tlogosari Wetan Health Center Semarang about 300 peoples. Samples selected purposively amount 17 people for each group. The intervention group was given 200 ml of soy milk per day for 14 days. The instruments used in this study were structured questionnaires, food recall 24 hours form with repetition, aneroid spygmomanometer, and MUAC tape. Data were analyzed using Wilcoxon Signed-Rank Test and Mann Whitney. The results have shown there were no differences in the characteristic of respondent (age, gravidity, educational level, ocuupational, income per capita, nutritional status, and nutrient intake) among groups. Systolic blood pressure before and after treatment in the two groups have significant differences, diastolic blood pressure before and after treatment differed only in the intervention group, whereas in the control group it didn’t. The decrease in systolic and diastolic blood pressure in the intervention group was higher than control group, with 10.59 mmHg differences. There were significant differences in changes in systolic and diastolic blood pressure between the two groups (p <0.05). Suggestions from this study are pregnant women can maintain their blood pressure by consuming soy milk regularly.